The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1136/bmj.295.6595.421
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus and drug misuse: the Edinburgh experience.

Abstract: During 1985 many drug abusers who lived in Edinburgh were found to be infected with the human immunodeficiency virus (HIV). As a result an alternative counselling and screening clinic for testing for antibodies to HIV was established for use by drug abusers. Four hundred and forty one patients were counselled in the first year, and over 60% were either drug abusers or their sexual contacts. One hundred and fourteen (26%) patients were positive for HIV antibody, and 100 (88%) ofthese were current or former drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The mean age at which they had begun injecting on a regular (that is, weekly) basis was 22; they had been injecting for a mean of seven years. Of 111 patients questioned, only six had not been introduced to injecting by another drug user; the rest had been helped to inject on the first occasion by friends (62), partners (25), acquaintances (13), or dealers (five). This was also the occasion when most had first shared needles and syringes: 75 patients had shared on the first occasion of injecting.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age at which they had begun injecting on a regular (that is, weekly) basis was 22; they had been injecting for a mean of seven years. Of 111 patients questioned, only six had not been introduced to injecting by another drug user; the rest had been helped to inject on the first occasion by friends (62), partners (25), acquaintances (13), or dealers (five). This was also the occasion when most had first shared needles and syringes: 75 patients had shared on the first occasion of injecting.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the 'Dutch distinction' is also present in part of the United States drug user population suggests that this particular variant may have originated from the United States, and then having crossed the Atlantic subsequently spread among Dutch, German and Scottish, and some Italian drug users. A sizeable proportion of Amsterdam drug users are German or Italian; a study among Edinburgh drug users showed that several of them had shared needles in Amsterdam (Brettle et at., 1987). The source of the homosexual infection could be a different one.…”
Section: Discussionmentioning
confidence: 99%
“…One sample from a Scottish homosexual was negative for vpr despite repeated isolation attempts, so for vpr only four Scottish homosexual samples were available. Two Scottish samples from heterosexual women were assigned to the drug user group, because the Scottish epidemic is most severe among drug users (Brettle et al, 1987;Peutherer et al, 1985), and because in northern Europe the largest risk factor for women who do not use intravenous drugs is sexual contact with a drug user. Both samples yielded a V3 sequence that was unmistakably of the drug user type.…”
Section: Other Northern European Samplesmentioning
confidence: 99%
“…In the U.K. only 118 cases of AIDS had been reported amongst intravenous drug users up to 31 December 1989, but 1,819 reports of HIV positive intravenous drug users had been received. A large proportion of these have been reported in Edinburgh where a substantial level of infection (at least 50% seropositive) has developed amongst the population of intravenous drug users (Robertson et al, 1986;Brettle et al, 1987;Hart et al, 1989). 8.7 The prevalence of HIV infection amongst intravenous drug users in some parts of the U.S.A. has lead to a serious public health problem (Weinberg & Murray, 1988).…”
Section: Blood Productsmentioning
confidence: 97%